2022
DOI: 10.1111/infa.12498
|View full text |Cite
|
Sign up to set email alerts
|

Expectant mothers' not fathers' mind‐mindedness predicts infant, mother, and father conversational turns at 7 months

Abstract: Parental mind-mindedness (MM), defined as the propensity to view one's child as an agent with thoughts, feelings, and desires, is associated with positive child outcomes (McMahon & Bernier, 2017) and can be assessed in expectant parents by using five-minute speech samples (Magaña et al., 1986). Individual differences in MM appear stable across the transition to parenthood (Foley et al., in press), offering an exciting intervention opportunity, as expectant mothers' thoughts and feelings about their unborn infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…These findings contrast with other longitudinal associations which differed by infant gender. For example, we have previously reported that, in this sample, gains in the theoretically related construct of mind‐mindedness were stronger in the postpartum period for fathers (not mothers) with daughters and not sons (Foley et al., 2022) and that mothers with poorer relationships with their partners at 4 months postpartum spoke more to their sons but not daughters at 7 months (Fink et al., 2020). Meta‐analytic studies have also examined whether parent and infant behaviors differ by infant gender (Endendijk et al., 2016); we hope that it will soon be possible to apply meta‐analyses to test more nuanced questions surrounding whether transactional links between parent and infant behavior systematically differ by infant gender.…”
Section: Discussionmentioning
confidence: 67%
“…These findings contrast with other longitudinal associations which differed by infant gender. For example, we have previously reported that, in this sample, gains in the theoretically related construct of mind‐mindedness were stronger in the postpartum period for fathers (not mothers) with daughters and not sons (Foley et al., 2022) and that mothers with poorer relationships with their partners at 4 months postpartum spoke more to their sons but not daughters at 7 months (Fink et al., 2020). Meta‐analytic studies have also examined whether parent and infant behaviors differ by infant gender (Endendijk et al., 2016); we hope that it will soon be possible to apply meta‐analyses to test more nuanced questions surrounding whether transactional links between parent and infant behavior systematically differ by infant gender.…”
Section: Discussionmentioning
confidence: 67%